2016
DOI: 10.14716/ijtech.v7i8.6886
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Renewable Diesel from Palm Oil and Jatropha Curcas Oil through Hydrodeoxygenation using NiMo/Zal

Abstract: Hydrodeoxygenation of palm oil and Jatropha curcas oil over NiMo/ZAL (nickel molybdenum/zeolit alam Lampung) catalyst was investigated under temperatures of 375°C and 400°C and H 2 pressure of 15 bar in a semibatch stirred autoclave reactor. NiMo/ZAL catalyst was prepared using a rapid cooling method. NiMo/ZAL characterization revealed a crystal size of 70.07 nm, surface area of 12.25 m 2 /g, and pore size and pore volume of 9.83 Å and 0.0062 cm 3 /g, respectively. The hydrodeoxygenation removal pathway of pal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…The SEM-EDS results showed that the NiMo/Al2O3 catalyst had a composition of 6.13% w/w Ni, 12.49% w/w Mo, and 81.33% w/w Al2O3. This showed that the reactive site for this catalyst was molybdenum, which has proven to be effective for hydrodeoxygenation, thus, producing C18 (Susanto et al, 2016). Nickel is effective for decarboxylation and decarbonylation, which produce C17.…”
Section: Resultsmentioning
confidence: 99%
“…The SEM-EDS results showed that the NiMo/Al2O3 catalyst had a composition of 6.13% w/w Ni, 12.49% w/w Mo, and 81.33% w/w Al2O3. This showed that the reactive site for this catalyst was molybdenum, which has proven to be effective for hydrodeoxygenation, thus, producing C18 (Susanto et al, 2016). Nickel is effective for decarboxylation and decarbonylation, which produce C17.…”
Section: Resultsmentioning
confidence: 99%
“…The decrease of viscosity caused by the breaking of carboxylic bond from the waste cooking oil containing carbonyl (CO) and hydroxyl (-OH). The presence of a hydroxyl group on a carboxylic bond may form a hydrogen bond with a carbonyl group that causes the bonding between molecules become stronger and higher viscosity value [8].…”
Section: Viscosity Of Bioavturmentioning
confidence: 99%
“…Kaewmeesri et al (2015) reported Ni/γ-Al2O3 catalysts for the methyl palmitate HDO reaction with a conversion of 60% and alkane C10-C12 selectivity of 58%. Research conducted by Ma and Zhao (2015) using nickel-metal nanoparticles embedded in Hierarchica Beta Zeolite (HBEA) zeolite catalyst showed the total yields of n-octadecane (C18) kept stable at 70 wt% after one h. By using palm oil as feedstocks, Susanto et al (2016) tested NiMo/ZAL (Clinoptilolite type) catalyst for hydrodeoxygenation reaction under hydrogen pressure of 15 bar and temperature of 375°C. The result showed that the renewable diesel yield (C13-C19) produced a conversion of around 80.87% and selectivity of 52.78%.…”
Section: Introductionmentioning
confidence: 99%